2016
DOI: 10.1530/erc-16-0160
|View full text |Cite
|
Sign up to set email alerts
|

The AR/NCOA1 axis regulates prostate cancer migration by involvement of PRKD1

Abstract: Due to the urgent need for new prostate cancer (PCa) therapies, the role of androgen receptor (AR)-interacting proteins should be investigated. In this study we aimed to address whether the AR coactivator nuclear receptor coactivator 1 (NCOA1) is involved in PCa progression. Therefore, we tested the effect of long-term NCOA1 knockdown on processes relevant to metastasis formation. [ 3 H]-thymidine incorporation assays revealed a reduced proliferation rate in AR-positive MDA PCa 2b and LNCaP cells upon knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…NCOA1 overexpression has been demonstrated in multiple cancers. 47,[51][52][53][54][55] The elevated levels of NCOA1 mRNA and increased gene copy number of NCOA1 found in this research suggest that both gene amplification and increased transcription could be part of the underlying mechanisms of NCOA1 overexpression in human ESCC. In addition, Cox analysis showed that the protein levels of NCOA1 are inversely proportional to ESCC patient survival.…”
Section: Discussionmentioning
confidence: 65%
“…NCOA1 overexpression has been demonstrated in multiple cancers. 47,[51][52][53][54][55] The elevated levels of NCOA1 mRNA and increased gene copy number of NCOA1 found in this research suggest that both gene amplification and increased transcription could be part of the underlying mechanisms of NCOA1 overexpression in human ESCC. In addition, Cox analysis showed that the protein levels of NCOA1 are inversely proportional to ESCC patient survival.…”
Section: Discussionmentioning
confidence: 65%
“…PPARGC1A is a transcriptional coactivator that regulates the genes involved in energy metabolism and is associated with aggressive prostate cancer . NCOA1 is a transcriptional coactivator for steroid and nuclear hormone receptors where the AR/NCOA1 axis regulates prostate cancer migration by involvement of PRKD1 …”
Section: Resultsmentioning
confidence: 99%
“…49 NCOA1 is a transcriptional coactivator for steroid and nuclear hormone receptors where the AR/NCOA1 axis regulates prostate cancer migration by involvement of PRKD1. 50 Many intronic variants were found on LGALS8, ABL2, PDE4B, and IL6R (Supporting Information 2). It has been reported that microRNA-20a promotes invasive prostate cancer by targeting ABL2.…”
Section: Cacna1cmentioning
confidence: 99%
“…Moreover, NCOA1 could promote angiogenesis in breast tumors by simultaneously enhancing both HIF1α- and AP-1-mediated VEGF-a transcription [31]. NCOA1, as the androgen receptor (AR) coactivator, was found to be involved in prostate cancer progression, while NCOA1 knockdown induced a significant decrease in migration and invasion through the upregulation of protein kinase D1 (PRKD1) [32]. Besides, NCOA1 expression was shown to have prognostic significance in advanced-stage head and neck carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%